2018
DOI: 10.1021/acs.jproteome.7b00821
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Multiorgan Samples: Evaluation of MODY5/RCAD Mutant Mice

Abstract: In the present study, we performed a metabolomics analysis to evaluate a MODY5/RCAD mouse mutant line as a potential model for HNF1B-associated diseases. Gas chromatography time-of-flight mass spectrometry (GC-TOF-MS) of gut, kidney, liver, muscle, pancreas, and plasma samples uncovered the tissue specific metabolite distribution. Orthogonal projections to latent structures discriminant analysis (OPLS-DA) was used to identify the differences between MODY5/RCAD and wild-type mice in each of the tissues. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Metabolic profiling of different organs, including kidney, pancreas and liver, as well as plasma of adult Hnf1 Sp2/+ mice, was previously reported ( Torell et al, 2018 ). We found evidence of impaired amino acid renal metabolism and reduced plasma levels of total free amino acids and increased myo-inositol, which are metabolic parameters reflecting impaired renal function, together with disturbed hepatic metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…Metabolic profiling of different organs, including kidney, pancreas and liver, as well as plasma of adult Hnf1 Sp2/+ mice, was previously reported ( Torell et al, 2018 ). We found evidence of impaired amino acid renal metabolism and reduced plasma levels of total free amino acids and increased myo-inositol, which are metabolic parameters reflecting impaired renal function, together with disturbed hepatic metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…We considered JIVE (joint and individual variation explained), DISCO-SCA (distinctive and common components with simultaneous-component analysis), and JUMBA (joint and unique multiblock analysis; a method based on OnPLS) [ 31 ]. From our previous research, we have found the dataset to contain the locally joint variation since the gut was not as affected by the mutation [ 25 ], therefore we were interested in methods that can handle both globally joint and locally joint, as well as unique variation. DISCO-SCA and JUMBA are both able to extract all three kinds of variations while JIVE is only able to extract the globally joint and unique variation.…”
Section: Discussionmentioning
confidence: 99%
“…The MODY5/RCAD mice were found to be characterized by higher levels of amino acids and fatty acids in the organs (kidney, liver, muscle, and pancreas) and lower levels of amino acids in the plasma. It has previously been shown that the gut was less affected by the mutation than the other studied tissue types [ 25 ]. This is in part due to the fact that the mutation affects a protein, hepatocyte nuclear factor 1b (hnf1b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered JIVE (joint and individual variation explained), DISCO-SCA (distinctive and common components with simultaneous-component analysis) and JUMBA (joint and unique multiblock analysis; a method based on OnPLS) [31]. From our previous research we have found the dataset to contain locally joint variation since gut was not as affected by the mutation [25], therefore we were interested in methods that can handle both globally joint, locally joint and unique variation. DISCO-SCA and JUMBA are both able to extract all three kinds of variation while JIVE is only able to extract globally joint and unique variation.…”
Section: Discussionmentioning
confidence: 99%